The Inspection Panel : Annual Report, August 1, 2001 to June 30, 2002 - World Bank (Inspection Panel Annual Reports, 2002)
This Annual Report covering the period August 1, 2001 to June 30, 2002, has been prepared by the members of the Inspection Panel for the International Bank for Reconstruction and Development and the International Development Association in accord with resolution authorizing it to provide independent judgment in cases where it is asserted that the rights and interests of parties are adversely affected by the Bank's failure to follow its operating policies and procedures in the design, appraisal, and/or implementation of Bank lending operations. In fiscal year 2002, the Panel received and registered three new Requests for Inspection relating to 1) The Uganda Third Power Project and the subsequently approved Bujagali Hydropower Project; 2) the Papua New Guinea Governance Promotion Adjustment Loan; and 3) the Paraguay Reform Project for the Water and Telecommunications Sectors and the Argentina SEGBA V Power Distribution Project. Also, the Panel continued work on the two Requests received in fiscal 2001: the Chad Petroleum Development and Pipeline Project, and the India Coal Sector Environmental and Social Mitigation Project. In this year, the Panel also continued work on revisions of its 1994 Operating Procedures, and in response to the Executive Directors'stated desire to make the Panel better known, the Panel continued its outreach efforts